The Physical Fitness Level of Participants in The Pencak Silat Extracurricular Activity at SMA Negeri 2 Ponorogo Post the Covid-19 Pandemic - Nugroho, Fajar Feri; Hamdani, Hamdani (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Pencak silat is one of the most popular extracurricular activities at SMA Negeri 2 Ponorogo. Pencak silat is also a sport that is quite popular among the people in the Ponorogo Regency itself. Therefore, students at SMA Negeri 2 Ponorogo take advantage of the pencak silat extracurricular which is also superior in achievement at the school. But after the worldwide disaster due to the impact of the corona virus, extracurricular activities were also hampered due to a long pandemic. Previously, extracurricular participants had superior achievements due to routine training activities, so they experienced a decline in achievement due to the covid-19 pandemic. If achievements can excel, surely every extracurricular participant before the pandemic must have good physical condition. But a test has never been carried out to find out whether the students' physical condition is good or not. Therefore, after this pandemic, researchers want to conduct a physical test survey through MFT which aims to determine the level of physical condition of extracurricular participants. The test can also be used as aalt to find out why the achievements of extracurricular participants have decreased after the co-19 pandemic.